Analysis of ohmic quality factor for the azimuthally symmetrical TE 03-mode 42GHz gyrotron cavity - Singh R.K.; Jain P.K.; Basu B.N. (My University, 2025)
A simple electromagnetic method has been presented, by dividing the input- and output-taper sections of cavity into numbers of non-tapered circular steps, to calculate the ohmic quality factor of tapered cavity of a 42 GHz, TE 03-mode gyrotron. The energy stored in cavity and power loss on cavity-wall, have been estimated in sinusoidal field profile. For the typically chosen non-tapered cavity, the calculated value of ohmic quality factor, in the present paper, was found within 4% of the results calculated using two of previously published expressions. The validation/ comparison of results against simulation software: MAGIC have been made and found within 3%. Further, the effect of structure dimensions, namely, length of mid-section of the cavity, input-taper angle and output-taper angle, on value of the ohmic quality factor for a tapered gyrotron cavity have been studied. It is found that the ohmic quality factor for a tapered gyrotron cavity, other parameters remaining constant, increases with decrease of length of mid-section and input-taper angle, and with increase of output-taper angle. Out of input- and output-taper angles, the latter was found more sensitive controlling parameter for the ohmic quality factor and hence frequency selectivity as well as ohmic heating in a tapered cavity. Furthermore, the contours of length of mid-section and ohmic quality factor were plotted to provide flexibility to the designer in optimising the structure parameters of tapered cavity of a 42 GHz, TE03-mode gyrotron. © 2007 IEEE.